Intrasaccadic perception triggers pupillary constriction - Mathôt, Sebastiaan; Melmi, Jean-Baptiste; Castet, Eric (PeerJ PrePrints, 2015)
It is commonly believed that vision is impaired during saccadic eye movements. However, here we report that some visual stimuli are clearly visible during saccades, and trigger a constriction of the eye's pupil. Participants viewed sinusoid gratings that changed polarity 150 times per second (every 6.67 ms). At this rate of flicker, the gratings were perceived as homogeneous surfaces while participants fixated. However, the flickering gratings contained ambiguous motion: rightward and leftward motion for vertical gratings; upward and downward motion for horizontal gratings. When participants made a saccade perpendicular to the gratings' orientation (e.g., a leftward saccade for a vertical grating), the eye's peak velocity matched the gratings' motion. As a result, the retinal image was approximately stable for a brief moment during the saccade, and this gave rise to an intrasaccadic percept: A normally invisible stimulus became visible when eye velocity was maximal. Our results confirm and extend previous studies by demonstrating intrasaccadic perception using a reflexive measure (pupillometry) that does not rely on subjective report. We suggest that visual perception during saccades is best understood in terms of predictive coding: The retinal motion that occurs during saccades is predictable, offers no evidence for motion in the environment, and is therefore not perceived. But when intrasaccadic visual input violates predictions, a clear intrasaccadic percept arises.
Keywords: pupillometry; intrasaccadic perception; saccadic suppression; eye movements; experimental psychology; vision science